Financial analysis of liquidity ratio performance on bank panin’s health for the 2019 – 2023 period with loan to deposit ratio (ldr) as the indicator - Marom, Ahmad Aufal (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze Bank Panin’s liquidity performance during the 2019–2023 period with Loan to Deposit Ratio (LDR) as the main indicator. The focus of the study is to evaluate Bank Panin’s ability to maintain a balance between lending and managing third party funds amidst external challenges, such as the COVID-19 pandemic and global market dynamics. The data used is Bank Panin’s annual financial report, with a descriptive qualitative approach. The results of the analysis show that although Bank Panin’s LDR ratio fluctuated during this period, the bank was still able to maintain its position within healthy limits in accordance with Bank Indonesia regulations (78–92%). The decline in the LDR ratio in 2020 reflects the impact of the pandemic on economic activity, but was followed by a significant recovery in the following years. Factors that influence liquidity performance include the bank’s internal strategy, macroeconomic conditions and banking regulations. This research provides important insights into how effective liquidity management can help banks overcome external and internal challenges. In addition, these findings are expected to become a reference for developing more adaptive liquidity strategies in the future as well as enriching literature in the field of banking financial management.